PERBEDAAN JUMLAH MIKROBA PADA ALAT MAKAN SEBELUM DAN SESUDAH DICUCI DENGAN DAUN JERUK PURUT (Citrus histrik. DC) - Sulistiyani . .; Ulfa . Nurullita; Dina Dwi Nuryani (Universitas Muhammadiyah Semarang, 2004)
ABSTRACT Background: Food tools can be a medium of diseases transmission if they are not washed cleanly. To prevent diseases transmission through food dishes are usually done by washing them some detergents or sanitizers. This way can produce waste water and cause environment pollution. (using natural substances (Citrus histrix leal) can reduce the polluted environment and microbe density on food dishes. This kind of leaf consists of polifenol, saponin, and atsiri oil to be functioned as disinfectants. Objective; This research is to count and analyze the difference of total microbe on the food dishes before and after being washed by Citrus histrix leaf. Method: This explanatory research applies the quasi experimental design, one group pretest posttest. Result; Total, microbes on food dishes before being washed by Citrus histrix leaf are t 13.2 x103 colony per cm2 and 9.7 x l03 after being washed. Statistical analysis by paired samples t test shows the signifiiant difference of microbe number (p = 0.000). Conclusion ; Citrus histrix leaf can reduce microbe density on the food dishes Keywords : Total of microbe, food dishes, Citrus histrix leaf